(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mesrian DK, Purwaningtyas WE, Astuti RI, Hasan AEZ, Wahyudi AT. 2021. Methanol pigment extracts derived from two marine actinomycetes exhibit antibacterial and antioxidant activities. Biodiversitas 22: 4440-4447. In recent years, natural pigments produced by marine microorganisms, especially actinomycetes, have become an important source of medically valuable drugs and other active compounds. Based on that crucial fact, this study aimed to determine the toxicity, antimicrobial, and antioxidant activities of methanolic pigment extract derived from marine actinomycetes HV11.P3 and SCA54.P2. Both extracts exhibited high toxicity activity based on Brine Shrimp Lethality Test (BSLT). The results showed the lethal concentration 50% (LC50) values of actinomycetes HV11.P3 and SCA54.P2 pigment crude extracts were 94.60 µg/mL and 131.22 mg/mL, respectively. The antimicrobial activity of those extracts was also tested against several microbes and showed the best results for inhibiting against Bacillus subtilis and Escherichia coli. Furthermore, we assessed the antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals and the results showed the inhibitory concentration 50% (IC50) values ??of actinomycetes HV11.P3 and SCA54.P2 pigment crude extracts were 231.08 µg/mL and 369.3 µg/mL, respectively. By using GC-MS analysis, we identified chemical compounds of actinomycete pigment crude extracts, revealing that the most dominant compounds were 1H-Purine-2,6-dione, 3,7-dihydro-1,3,7-trimethyl- (CAS) (44.65%) for HV11.P3 and 5-Methoxypyrrolidin-2-one (30.23%) for SCA54.P2. The 16S rRNA gene sequence analysis showed that actinomycete HV11.P3 and actinomycete SCA54.P2 had the closest similarity to Micromonospora chalcea strain 1464-217L and Micromonospora tulbaghiae strain TVU1, respectively. This study revealed that two pigment crude extracts derived from actinimycetes HV11.P3 and SVA54.P2 had antibacterial, antioxidant, and toxicity activities. The actinomycete SCA54.P2 pigment crude extract had the best activity as an antibacterial against E. coli ATCC 8739, while actnomycete HV11.P3 pigment crude extract had the best activity as an antioxidant.